1980
DOI: 10.1017/s0022215100089945
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the nerve endings of the outer and inner hair cells in the organ of Corti

Abstract: The synaptic region and nerve endings have been studied both in the outer and inner hair cells by using optic and electron microscopy, nerve staining and Acetyl Cholinesterase activity. The findings are described, with a discussion of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous results 14 have shown that, as well as adrenergic innervation, the organ of Corti receives sensory input via afferent and efferent nerve fibres within the central nervous system. The efferent nerve fibres are distributed mainly among the outer hair cells, with which they make synaptic contacts by means of the nerve endings identified by Engström 15 (the morphological aspects of which have since been extensively studied) 16 . Functionally, the medial efferent fascicle carries signals capable of influencing the sensitivity of the peripheral auditory system, specifically with respect to frequency, through its action on the dynamics of the basilar membrane (analysed by means of in vivo studies) 17 …”
Section: Discussionmentioning
confidence: 99%
“…Previous results 14 have shown that, as well as adrenergic innervation, the organ of Corti receives sensory input via afferent and efferent nerve fibres within the central nervous system. The efferent nerve fibres are distributed mainly among the outer hair cells, with which they make synaptic contacts by means of the nerve endings identified by Engström 15 (the morphological aspects of which have since been extensively studied) 16 . Functionally, the medial efferent fascicle carries signals capable of influencing the sensitivity of the peripheral auditory system, specifically with respect to frequency, through its action on the dynamics of the basilar membrane (analysed by means of in vivo studies) 17 …”
Section: Discussionmentioning
confidence: 99%